Untargeted Metabolomics: Biochemical Perturbations in Golestan Cohort Study Opium Users Inform Intervention Strategies - Li, Yuan-Yuan; Ghanbari, Reza; Pathmasiri, Wimal; McRitchie, Susan; Poustchi, Hossein; Shayanrad, Amaneh; Roshandel, Gholamreza; Etemadi, Arash; Pollock, Jonathan D.; Malekzadeh, Reza; Sumner, Susan C. J. (Frontiers in Nutrition, 2020)
Objective: Over 50 million people worldwide are estimated to use opioids, of which ~30 million use opiates (opium and its derivatives). Use of opiates has been associated with variety of adverse complications such as neurological and behavioral outcomes, addiction, cancers, diabetes, and cardiovascular disease. While it is well known that opiates exert their neurobiological effects through binding with mu, kappa, and delta receptors to exert analgesic and sedative effects, mechanistic links to other health effects are not well understood. Our study focuses on the identification of biochemical perturbations in Golestan Cohort Study (GCS) opium users. Methods: We used untargeted metabolomics to evaluate the metabolic profiles of 218 opium users and 80 non-users participating in the GCS. Urine samples were obtained from adult (age 40-75) opium users living in the Golestan Province of Iran. Untargeted analysis of urine was conducted using a UPLC-Q-Exactive HFx Mass Spectrometry and a 700 MHz NMR Spectrometry. Results: These GCS opium users had a significantly higher intake of tobacco and alcohol, and a significantly decreased BMI compared with nonusers. Metabolites derived from opium (codeine, morphine, and related glucuronides), nicotine, and curing or combustion of plant material were increased in opium users compared with non-users. Endogenous compounds which differentiated the opium users and non-users largely included vitamins and co-factors, and metabolites involved in neurotransmission, Kreb’s cycle, purine metabolism, central carbon metabolism, histone modification, and acetylation. Conclusions: Our study reveals biochemical perturbations in GCS opium users that are important to the development of intervention strategies to mitigate against the development of adverse effects of substance abuse.